The epidemiology of cryptorchidism and potential risk factors, including endocrine disrupting chemicals - Holmboe, Stine A.; Beck, Astrid L.; Andersson, Anna-Maria; Main, Katharina M.; Jørgensen, Niels; Skakkebæk, Niels E.; Priskorn, Lærke (Frontiers in Endocrinology, 2024)
Congenital cryptorchidism, also known as undescended testis, is the condition where one or both testes are not in place in the scrotum at birth and is one of the most common birth defects in boys. Temporal trends and geographic variation in the prevalence of cryptorchidism from 1% to -9% have been reported in prospective cohort studies. The testes develop in the abdominal cavity and descend to the scrotum in two phases, which should be completed by gestational week 35. Thus, the risk of cryptorchidism is higher in preterm boys. In many cases a spontaneous descent occurs during the first months of life during the surge of gonadotropins and testosterone. If not, the testis is usually brought down to the scrotum, typically by surgery, to increase future fertility chances and facilitate cancer surveillance.The increasing frequency of impaired semen quality and testicular cancer, with which cryptorchidism is associated, represents a concern for male reproductive health in general and a need to understand its risk factors. The risk of cryptorchidism is closely related to gestational factors (preterm birth, low birth weight and intrauterine growth restriction), and especially maternal smoking seems to be a risk factor. Evidence is accumulating that the increasing prevalence of cryptorchidism is also related to prenatal exposure to environmental chemicals, including endocrine disrupting compounds. This association has been corroborated in rodents and supported by ecological studies. Conducting human studies to assess the effect of endocrine disrupting chemicals and their interactions is, however, challenged by the widespread concomitant exposure of all humans to a wide range of chemicals, the combined effect of which and their interactions are highly complex.